ANALISIS SISTEM INFORMASI DIGITAL PELAYANAN INFORMASI PENUMPANG DI BANDAR UDARA SULTAN THAHA JAMBI - Sunaryo, Aisha Tabina Cahyarani; Kalbuana, Nawang; Faizal, Irwan (FTK UNSURYA, 2025)
The increase in the number of passengers at Sultan Thaha Airport has triggered the need for faster and more accurate information services. One of the digital information systems used is the Flight Information Display System (FIDS), which is managed through an internal website by information officers. This research aims to analyze the factors that cause FIDS to not provide maximum service, identify features that need to be added, and examine the integration of Flight Information Display System (FIDS) with Public Address System (PAS) and Automatic Announcement System (AAS). This research uses a qualitative descriptive method with data collection techniques through observation, documentation, and interviews. The results showed that the main obstacles lie in data input errors, delays in information updates, less legible FIDS displays, and unstrategic screen locations. In addition, the absence of integration between FIDS and PAS makes information not delivered simultaneously. In conclusion, the FIDS system needs to be improved through officer training, development of real-time dashboard features, and automatic integration with PAS and AAS to improve information services that are fast, accurate, and user-friendly.